Model parenting Islami untuk Optimalisasi Tumbuh Kembang Anak Usia Dini - Juni Hati Hangoluan Siregar; Nurtia Sumarni Hasibuan; Masganti Sit (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Early childhood development (0–6 years) is a critical period that shapes a child’s physical, cognitive, socio-emotional, language, and moral growth. The family, as the first educational environment, plays a vital role in shaping the child’s character and adaptive skills, particularly through parent–child interactions. In Muslim communities, child-rearing focuses on not only psychological aspects but also reinforcing religious values through Islamic Parenting, which is based on the principles of rahmah (compassion), uswah (exemplary behavior), guidance, and ‘adl (justice), as outlined in the Qur’an and Hadith. This study uses a qualitative literature review to analyze the role of Islamic Parenting in early childhood development, highlighting the significance of these values. The review shows that Islamic Parenting plays a crucial role in optimizing children’s holistic development, including cognitive, social, emotional, moral, and spiritual aspects. Key components of this model include parental exemplification, compassion, religious education, positive behavior habituation, and cognitive stimulation through educational interactions. This model can be implemented through daily practices such as prayers, storytelling, and character reinforcement. In conclusion, Islamic Parenting fosters not just biological caregiving but also character, morality, and spirituality, preparing children for contemporary challenges.